Research on Durability of Paint and Varnish Coatings Depending on the Quality of Their Appearance - Loganina, Valentina (Advanced Aspects of Engineering Research Vol. 4, 2021)
The aim of the work is to study the regularities of the influence of the quality of the appearance of coatings on their durability during the operation. Object of research - paint and varnish coatings of building products and construction. Information on the effect on the longevity of coatings of the quality of their appearance is given. It is shown, that coatings with a high roughness index are characterized by low durability during exploitation. Are revealed the influence of the rheological properties of the paint, the porosity of the substrate on the surface roughness of the coatings. Determined, that regardless of the type of paint composition, the strength and relative deformations are reduced, the plastic deformation is increased and the elastic deformation are reduced with increasing roughness of surfaces. A mathematical model is obtained of the dependence of the tensile strength on the roughness of the surface of the films. It is established, that during the moistening of the coatings in the first stage (up to 30 days), the roughness of the surface is reduced, i.e., the surface micro relief is levelled due to the plasticizing effect of moisture (swelling of the coatings). In the future, due to the destructive effect of moisture, the surface roughness increases, caused by the appearance of micro cracks, rashes, and bubbles. It is established, that in the process of cyclic freezing-thawing the cracks appear locally and are formed near defects on the surface of the coating. The researches allow to develop recommendations for increasing the resistance of coatings and to select the optimum rheological properties of paints depending on the porosity of the substrate.